“I Saw the Look on Her Face:” Engaging the “between” Spaces of Work with Refugee-Background Students and Families - Fruja, Ramona; Roxas, Kevin (Journal of Ethnic and Cultural Studies, 2025)
This paper bridges critical refugee studies concepts with the literature on refugee education, advancing the possibilities of humanizing educational discourses and practices for refugee youth and families. We consider educational practices that move beyond labels and seek what is possible in the “in-between” spaces that sustain agency to define the parameters of belonging and participation. We examine how educators’ and schools’ work needs to takes place between recognizing the refugee status and its implications and not reducing the person to that identity category; between supporting the refugee student in their needs, and yet not trapping the youth in that category indefinitely by inadvertently disallowing self-definition; between ensuring the needed service and supports, and yet accepting what refugee youth and their families have to offer to the institution and the educational process; between rejecting derogatory labels for refugees as ‘resource-takers’ and yet resisting the commodification of these youth as “resources” themselves. Amid framing discourses of idealizing and demonizing discourses of worthiness and danger, educators are invited into the “in-between” spaces that offer rich moves into belonging.